Superiority of dynamic stretching over static and combined stretching protocols for repeated sprint performance in elite male soccer players - Aouadi, R.; Ltifi, M. A.; Ceylan, H. I.; Jlid, M. C.; Bragazzi, N. L. (Sports, 2025)
This study aimed to examine the effects of different stretching techniques on repeated sprint performance and to assess the influence of the sequence in which static and dynamic stretching are performed. Ten male Division II soccer players (age: 22.80 ± 1.13 years; height: 180.60 ± 3.59 cm; body mass: 70.60 ± 6.04 kg) completed a repeated sprint test consisting of 6 × 30 m sprints after five different warm-up protocols in a randomized, counterbalanced design: (1) general warm-up without stretching (NS), (2) static stretching (SS), (3) dynamic stretching (DS), (4) SS followed by DS (SS-DS), and (5) DS followed by SS (DS-SS). Stretching was performed during the recovery periods between sprints: ~6 min for SS and DS, and ~12 min for combined protocols. Sessions were spaced 72 h apart. Performance metrics included mean sprint time, best sprint time, and total sprint time. ANOVA and Cohen`s d were used for statistical analysis. Repeated sprint test performance was significantly enhanced after DS compared to SS, DS-SS, and SS-DS (p = 0.042-0.002; ES = 0.31-2.26), but not significantly different from NS (p > 0.05). SS had a detrimental effect when compared to DS and NS (p < 0.05; ES = 1.86-2.26). Improvements were observed in mean sprint time and total sprint time across all six sprints (p = 0.042-0.006; ES = 0.31-2.26) and in best sprint time (p = 0.006-0.002; ES = 0.89-1.86). In conclusion, DS prior to repeated sprint test improves performance compared to SS and combined methods. NS also supports strong performance but shows a slight advantage over SS and combinations. Incorporating DS into warm-up routines is recommended to optimize sprint performance, reduce injury risk, and support athlete preparation.